Remote support to victims of violence against women and domestic violence during the COVID-19 pandemic - Almeida, Iris Sofia (The journal of adult protection, 2021)
Purpose – This paper aims to characterize the type of support provided to victims of violence against women and domestic violence (VAWDV) during the first lockdown, assessing the training of professionals to use remote support (RS). Design/methodology/approach – This cross-sectional study involves a sample of 196 support professionals, mainly women (91.8%) and who integrate the Portuguese National Support Network for victims of domestic violence (NSNVDV) (Mean age = 36.49; SD = 10.52). Findings – Telephone emerges as themain RS communication media used in the lockdown (43.9%) and the emergency state periods (57.1%). Participants reported to have never used any social applications (41.8% vs 41.8%) or videoconference (46.4% vs 58.2%), in both periods assessed, i.e. lockdown and emergency state, respectively, and 82.7% assumed to have no training with RS to assist VAWDV victims. However, support professionals recognized several advantages in using RS such as dealing with isolation, reducing inhibition, fear and shame and in promoting the victims’ empowerment. Research limitations/implications – Given the exploratory nature of this study, only descriptive analyzes were conducted. Originality/value – During the COVID-19 pandemic, little is known about effective RS given by professionals to victims of VAWDV in the Portuguese context. The paper aims to add knowledge to the studied field.info:eu-repo/semantics/publishedVersio